2022
DOI: 10.1155/2022/1822328
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Treated Wastewater on the Percentage of Protein Content during Fodder Intercropping

Abstract: This study aims to explore the potential use of treated wastewater in irrigating fodder crops and its effects on protein contents. A comparison of the protein contents in intercropped fodder plants irrigated with fresh water, and rainfall water, against those irrigated with treated grey water was performed under Palestinian climate conditions. Field experiments with different intercropping mixing ratios were carried out in 2017–2019 at the National Agricultural Research Centre in Palestine (NARC). Measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…These results agree with Bacchi (2021) who reported that incorporating legumes in forage mixtures with grasses enhanced the overall quality of the biomass, particularly in terms of protein content. The results are also in agreement with Houshia et al, (2022) whom indicated that intercropping barley with common vetch improved the forage quality and increased the protein yield of barley without reducing dry matter yield…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results agree with Bacchi (2021) who reported that incorporating legumes in forage mixtures with grasses enhanced the overall quality of the biomass, particularly in terms of protein content. The results are also in agreement with Houshia et al, (2022) whom indicated that intercropping barley with common vetch improved the forage quality and increased the protein yield of barley without reducing dry matter yield…”
Section: Discussionsupporting
confidence: 88%
“…Intercropping of two or more crops on the same field has been adopted to optimize irrigation parameters and maximize product benefits. The integration of legumes is an essential aspect of agricultural and animal feed systems, and legume-cereal intercropping, such as corn-beans intercropping, is commonly practiced in many parts of the world (Houshia et al, 2022).…”
Section: Discussionmentioning
confidence: 99%